Treatment Algorithm for Management of Benign Prostatic Obstruction: An Overview of Current Techniques - Hughes, Thomas; Harper, Philip; Somani, Bhaskar K. (Life (Basel, Switzerland), 2023)
The management of benign prostatic obstruction (BPO) should involve a treatment algorithm that takes into account prostate size, and patient’s symptoms and preference with the aim of helping with urinary symptoms and enhance quality of life. The diagnostic assessment for men with lower urinary tract symptoms (LUTS) should be comprehensive to help choose the best management strategy. Strategies from lifestyle modifications to medical treatment with alpha blockers and/or 5-alpha-reductase inhibitors to surgical procedures can all be used in the management algorithm. Surgical management ranges from transurethral resection of prostate (TURP) to minimally invasive surgical therapies (MIST) including laser therapies such as Holmium laser enucleation (HoLEP) and photoselective vaporisation (PVP), aquablation, Rezūm system, prostate artery embolisation (PAE), prostatic urethral lift (PUL), temporary implantable nitinol device (iTind) and Optilume BPH catheter system. BPO is a common urological condition that has a significant impact on quality of life and economic burden globally and is likely to become increasingly prevalent with an ageing population. Selecting the most appropriate treatment modality will depend on the individual patient preferences, availability of resources, cost, anatomical factors and the goals of treatment.